(untitled) (Bangladesh Journal of Nuclear Medicine, 2025)
Background: Autoimmune Polyglandular Syndrome Type 3 is a rare condition where patients are diagnosed with more than one autoimmune disease having similarity in pathogenesis. Antibody detection with various imaging modalities, including nuclear medicine techniques, is crucial to confirm the diseases. Case Report: A 61-year-old elderly postmenopausal woman presented with vitiligo, features of hypothyroidism and systemic lupus erythematosus (SLE). After proper clinical evaluation, the anti-TPO antibody report came out positive, and a cold nodule was found in thyroid scintigraphy, thus confirming the diagnosis of autoimmune thyroiditis. Conclusion: Autoimmune thyroiditis associated with vitiligo is more common in female individuals under APS Type 3, so screening is recommended for clinically manifested pathology. Bangladesh J. Nuclear Med. 28(1): 159-163, 2025